2020
DOI: 10.1002/per.2268
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the incremental value of personality facets: the domains-incremental facets-acquiescence bifactor showmodel

Abstract: Personality can be described at different levels of abstraction. Whereas the Big Five domains are the dominant level of analysis, several researchers have called for more fine-grained approaches, such as facet-level analysis. Personality facets allow more comprehensive descriptions, more accurate predictions of outcomes, and a better understanding of the mechanisms underlying trait-outcome relationships. However, several methodological issues plague existing evidence on the added value of facet-level descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 62 publications
(122 reference statements)
3
30
0
Order By: Relevance
“…This method has two key benefits: First, Big Five facets, explicitly constructed and validated as subscales of the Big Five domains, are conceptually and empirically part of the Big Five. This holds even though facets are—like most stand-alone scales—narrower in focus than the Big Five factors to which they belong, and thus often bring incremental predictive validity beyond the Big Five (e.g., Anglim et al, 2020; Danner et al, 2020). To the degree that a given stand-alone scale shows similar or even greater links with the Big Five than is observed for some Big Five facets, it would be reasonable to conclude that the stand-alone scale can be located within the Big Five, perhaps as a facet itself.…”
Section: The Big Five As An Organizing Framework For Psychological Tr...mentioning
confidence: 99%
“…This method has two key benefits: First, Big Five facets, explicitly constructed and validated as subscales of the Big Five domains, are conceptually and empirically part of the Big Five. This holds even though facets are—like most stand-alone scales—narrower in focus than the Big Five factors to which they belong, and thus often bring incremental predictive validity beyond the Big Five (e.g., Anglim et al, 2020; Danner et al, 2020). To the degree that a given stand-alone scale shows similar or even greater links with the Big Five than is observed for some Big Five facets, it would be reasonable to conclude that the stand-alone scale can be located within the Big Five, perhaps as a facet itself.…”
Section: The Big Five As An Organizing Framework For Psychological Tr...mentioning
confidence: 99%
“…Studies using other facets have observed that the Extraversion-SWB association was entirely driven by the Energy Level facet that contains items about being active and enthusiastic, whereas Assertiveness and Sociability facets played no roles at all. Of course, a correlation between low enthusiasm and low wellbeing is hardly surprising (Margolis, Stapley & Lyubomirsky, 2020;Danner, Lechner, Soto & John, 2020).…”
Section: Disadvantages and Benefits Of Facet-and Nuance-specific Analysesmentioning
confidence: 99%
“…Moreover, it is beneficial that the BFI-10 controls for acquiescence, which is a likely source of bias in the pSES–personality association because acquiescence is higher in individuals with lower education (Rammstedt et al, 2010 ) and lower cognitive ability (Lechner and Rammstedt, 2015 ). However, ultra-short measures such as the BFI-10 do not allow for facet-level analyses, which are often a more promising level of abstraction in trait–outcome research (e.g., Danner et al, 2020 ; Mõttus et al, 2020 ). Hence, it would be desirable for future research to revisit the interplay between pSES, socio-emotional skills, and achievement using faceted measures of personality.…”
Section: Limitationsmentioning
confidence: 99%